The characterisation of interstitial lung disease multidisciplinary team meetings: a global study. Issue 2 (1st April 2019) - Richeldi, Luca; Launders, Naomi; Martinez, Fernando; Walsh, Simon L.F.; Myers, Jeffrey; Wang, Bonnie; Jones, Mark; Chisholm, Alison; Flaherty, Kevin R.
Multidisciplinary team (MDT) diagnosis of interstitial lung disease (ILD) has been proposed as a gold standard, but there are no formal recommendations for MDT process or composition and limited knowledge regarding prevalence in routine practice. We performed a systematic evaluation of ILD diagnostic practice across a range of healthcare settings around the world. Electronic questionnaires were distributed across all global regions via society and collaborators networks. Responses from 457 unique centres across 64 countries were included in the analysis. Of the 350 (76.6%) centres holding formal meetings, the majority held face-to-face MDT meetings (80%), for a minimum of 30 min (93%), and discussed diagnosis (96.9%) and patient management (94.9%) at the meetings. Compared with non-academic and academic non-ILD centres, ILD academic centres reported a higher ILD caseload, held more formal MDT meetings, and were more likely to include histopathology and rheumatology specialists in their diagnostic team. Of the centres holding MDT meetings, 5.5% routinely discussed all new cases at such meetings. An MDT approach to ILD diagnosis is consistently interpreted and widely implemented across a range of routine care settings around the world. This observation will inform future ILD diagnostic agreement studies and diagnostic pathway recommendations. In real-world practice, ILD diagnosis uses a multidisciplinary team approach, irrespective of country or healthcare setting http://ow.ly/I1Di30nMNTX